ADSORPTION EQUILIBRIUM OF 2,4 DICHLOROPHENOL FROM WASTE WATERS ONTO ACTIVATED CARBON - Mihaela Neagu (Romanian Journal of Petroleum & Gas Technology, 2023)
The batch adsorption of 2,4-dichlorophenol from aqueous solution onto mesoporous activated carbon was investigated for a range of initial concentrations of 50 to 1000 mg/ L, at constant temperature of 293 K. The experimental adsorption isotherms were analyzed with two and three parameters models (i.e., Freundlich, Langmuir, Langmuir-Freundlich, and Brouers-Sotolongo models). The non-linear fitting method was employed for estimating the isotherm parameters. The standard statistical tools were used to check the accuracy of the fit measure, namely: the coefficient of determination R2, the adjusted coefficient of determination Adj- R2, the residual sum of squares RSS (or chi-square function χ2), and reduced chi-square Red- χ2. The analysis of all the isotherms found that the Brouers-Sotolongo model shows higher correlation coefficients of R2 and Adj-R2 values and lower values of RSS and Red-χ2. Also, the Brouers-Sotolongo model shows a maximum adsorption capacity qm of 50.46 mg/g, which is very close to the experimental data (48.123 mg/g) value. The adsorption process was mainly physical adsorption on heterogeneous surfaces. The heterogeneous surface of activated carbon was confirmed by FT-IR analysis, the Boehm method, and pHPZC, as presented in our previous studies. The interactions between 2,4 DCP and GAC are mostly a type of dispersion effect between the π electrons in the aromatic ring of the phenolic compound and the π electrons in the structure of the GAC adsorbent. Also, electrostatic attractions may occur between the π electrons in the aromatic rings of 2,4 DCP and the positive surface of the GAC.